Warehouse Optimization: Energy Efficient Layout and Design - Derpich-Contreras, I; Sepulveda-Salas, J; Castro-Cerda, F; Barraza-Alonso, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
It has been widely demonstrated by many research works that the distribution of a factory can condition its productivity. Because of this, a factory in Santiago, Chile, asked the authors for advice to evaluate the current situation in the company and what alternatives could be proposed to improve performance by increasing productivity without incurring too high costs. Among the most important requirements requested was a study of the current design of the raw materials warehouse within the plant since this is a main pillar in the design of the plant. For this purpose, the current layout ws analyzed and alternative designs were proposed under two scenarios: use the same area that is currently available or make the design from scratch considering land purchases to build the warehouse. In order to give a precise answer to many possible design decisions, formulations were developed and deduced to calculate the optimal dimensions of the warehouse, and qualitative criteria were incorporated for decision making. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.